Records and descriptions of some Nemouride species (Order: Plecoptera) from Leigong Mountain, Guizhou province, China - Wang, Zhi-Jie (Illiesia, 2006)
Three new species of Nemouridae, Amphinemura leigong Wang & Du, Indonemura trilongispina Du & Wang, and Nemoura oculata Wang & Du are described and illustrated from male specimens collected on Leigong Mountain in southeast Guizhou Province, China. New records from this area are also given for Amphinemura cordiformis Li & Yang, Nemoura guangdongensis Li & Yang and a Nemoura species being described elsewhere.
Keywords: insekti; Plecoptera; vrbnice; Kitajska